Legal Implications of Rejecting Divorce Petitions in the Perspective of Islamic Law and Positive Law in Indonesia : Case Study of Andre Taulany's Case in the Religious Court - Adikza Nurul Islam; Salsabila, Fajrina Dhia (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Divorce cases in Indonesia often reveal a tension between the fiqh concept of talak as a husband’s prerogative and the national legal system that requires judicial control. This study focuses on the repeated rejection of Andre Taulany’s divorce case to understand this legal dynamic. This research aims to analyze the judges’ legal considerations in rejecting divorce suits and to compare Islamic law and Indonesian positive law perspectives regarding such rejections. This study employs a normative juridical approach using case and statute approaches, with data derived from court decisions, fiqh literature, and relevant legislation. The findings indicate a fundamental difference between fiqh, which positions talak as a direct right of the husband, and Indonesian positive law, which requires judicial examination to ensure fairness and legal protection. The court’s authority to reject talak reflects efforts to achieve justice, protect women’s rights, and ensure that divorce occurs based on legitimate legal reasons